The Czechoslovak footprint in Subcarpathian Ruthenia - Loutocká, Vlasta (České vysoké učení technické v Praze, 2024)
Not long after the end of World War I, the then young Czechoslovakia was joined by Subcarpathian Ruthenia and a period of about twenty years began, during which many important buildings were constructed in this new part of the republic, whole new districts were created, as well as a number of industrial and transport buildings. Leading Czechoslovak experts worked on the projects, among them Adolf Liebscher, an architect, urban planner and teacher. Adolf Liebscher was not the only Czechoslovak architect to work in Subcarpathian Ruthenia. However, this promising development was forcibly interrupted in 1938 and this short historical phase fell into oblivion. Today, after the collapse of the Soviet Union, the inhabitants of the former Subcarpathian Ruthenia are again becoming interested in the time when they were part of Czechoslovakia, and a number of associations are working, which commemorates the Czechoslovak trace, especially in Uzhhorod. Unfortunately, this process is currently being violently interrupted by the war unleashed by an aggressive Russia.

Not long after the end of World War I, the then young Czechoslovakia was joined by Subcarpathian Ruthenia and a period of about twenty years began, during which many important buildings were constructed in this new part of the republic, whole new districts were created, as well as a number of industrial and transport buildings. Leading Czechoslovak experts worked on the projects, among them Adolf Liebscher, an architect, urban planner and teacher. Adolf Liebscher was not the only Czechoslovak architect to work in Subcarpathian Ruthenia. However, this promising development was forcibly interrupted in 1938 and this short historical phase fell into oblivion. Today, after the collapse of the Soviet Union, the inhabitants of the former Subcarpathian Ruthenia are again becoming interested in the time when they were part of Czechoslovakia, and a number of associations are working, which commemorates the Czechoslovak trace, especially in Uzhhorod. Unfortunately, this process is currently being violently interrupted by the war unleashed by an aggressive Russia.
The Czechoslovak footprint in Subcarpathian Ruthenia
Keywords: Subcarpathian Ruthenia; Adolf Liebscher; Maly Galagov; interwar architecture; Subcarpathian Ruthenia; Adolf Liebscher; Maly Galagov; interwar architecture